Source localization and functional network analysis in emotion cognitive reappraisal with EEG-fMRI integration - Li, Wenjie; Zhang, Wei; Jiang, Zhongyi; Zhou, Tiantong; Xu, Shoukun; Zou, Ling (Frontiers in Human Neuroscience, 2022)
Background: The neural activity and functional networks of emotion cognitive reappraisal have been widely investigated by using Electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). However, single-mode neuroimaging techniques are limited in exploring the regulation process with high temporal and spatial resolution. Objectives: We proposed a source localization method with multimodal integration of EEG and fMRI, and tested it in the source-level functional network analysis of emotion cognitive reappraisal. Methods: EEG and fMRI data were simultaneously recorded when fifteen subjects were performing the emotion cognitive reappraisal task. Fused priori weighted minimum norm estimation (FWMNE) with sliding windows was proposed to trace the dynamics of EEG source activities, and phase lag index (PLI) was used to construct the functional brain network associated with the process of down-regulating negative affect using the reappraisal strategy. Results: The Source activity contrast of “reappraisal > watch” revealed significant activation transfer from inferior parietal lobe, inferior middle frontal gyrus, insular to superior temporal gyrus, lateral occipital lobule, and at last in inferior middle frontal gyrus, fusiform gyrus, and isthmus of cingulate gyrus. In the gamma band source-level network analysis, cuneus, lateral orbitofrontal cortex, superior parietal cortex, postcentral gyrus, and pars opercularis were identified as important regions in reappraisal with high betweenness centrality. Conclusion: The proposed multimodal integration method for source localization identified the key cortices involved in emotion regulation, and the network analysis demonstrated the important brain regions involved in the cognitive control of reappraisal. It shows promise in the utility in the clinical setting for affective disorders.